Editorial - Abreu, José G. (CAP - Cadernos de Arte Pública / Public Art Journal, 2020)
Since 20th century’s last decades, public art, and its youngest expression, street art, have been obtaining increasing impact on non-specialized audiences, and gaining greater attention by critics and other specialists, for public art is the artistic discipline “that characterizes best the manifestations of the last third of the 20th century” (Maderuelo, 2000:240). Nowadays, there is no urban improvement, no architectonic iconic intervention, no landscape project, no heritage revitalization initiative that do not have, as its expected consequence, public space redesign and public art display. Meant as one of the main urban regeneration tools, public art has been contributing to transform the 20th century industrial-functional city into the convivial cities of post-industrial era (Miles, 1997). Present in art schools and university curricula, where it engages increasing advanced studies, when talking about Public Art now, we think the time has come to gather, to analyze and to reflect upon what has been done, in order to generate new synthesis, about what this novel, and yet very old domain, has achieved. Engaging Public Art a progressive ideario (Armajani, 1995), has anything carrying social relevance really changed in our cities? Did public art succeed in catalyzing meaning to our common ground of interaction? How do social sciences assess the outcomes of globalized public space aesthetical gaze and use? And talking about meaning, is public art fostering social inclusion of multi-ethnic minorities and avant-garde thinking or action? As all utopian project, is public art inspiring the creation of new and more rewarding goals to our culture? Obviously, these aims are not supposed to be achieved by a couple of articles in a single journal. So, let me express our goals in a most humble way, as Hannah Arendt did, when she said that “what I propose, therefore, is very simple: it is nothing more than to think what we are doing.” (Arendt, 1958:5)